Effects of 7E Instructional Model with Metacognitive Scaffolding on Students’ Conceptual Understanding in Biology - Habtamu Wodaj; Solomon Belay (Journal of Education in Science, Environment and Health)
The main aim of this study was to explore the effect of 7E instructional model with metacognitive scaffolding and gender on 9th grade students’ conceptual understanding of human biology concepts and misconceptions. The research method was a quantitative research method and the research design was quasi-experimental research design with pre-test – treatment – post-test. The study was conducted on four purposely selected schools and four classes and teachers (one from each school) and assigned as treatment group 1, treatment group 2, treatment 3 and comparison group randomly. These groups were instructed with 7E instructional model alone, 7E instructional model with metacognitive scaffolding, conventional approach with metacognitive scaffolding and conventional approach respectively to teach human biology for 10 weeks. Human biology conceptual understanding test was administered for all groups as pre-test and post- test. The ANOVA results showed that 7E instructional model supported with metacognitive strategies had a significantly superior effect over the other instructional methods for enhancing students’ conceptual understanding and minimizing misconceptions. However, no significant difference was found between males and females in students’ conceptual understanding. Hence, metacognitive scaffolding with 7E instructional model could help students to understand biology concepts and minimize misconceptions better than the other instructional methods.